Drought Risk Assessment in the Khushab Region of Pakistan Using Satellite Remote Sensing and Geospatial Methods: Drought Risk Assessment in the Khushab Region of Pakistan Using Satellite Remote Sensing and Geospatial Methods - Abuzar, Muhammad Khubaib; Shafiq, Muhammad; Mahmood, Syed Amer; Irfan, Muhammad; Khalil, Tayyaba; Khubaib, Nusaiba; Hamid, Amna; Shaista, Sobia (International Journal of Economic and Environmental Geology, 2019)
Drought is a harmful and slow natural phenomenon that has significant effects on the economy, social life, agriculture and environment of the country. Due to its slow process it is difficult to study this phenomenon. Remote Sensing and GIS tools play a key role in studying different hazards like droughts. The main objective of the study was to investigate drought risk by using GIS and Remote Sensing techniques in district Khushab, Pakistan. Landsat ETM images for the year 2003, 2009 and 2015 were utilized for spatial and temporal analysis of agricultural and meteorological drought. Normalized difference vegetation index (NDVI) Standardized Precipitation Index (SPI) and rainfall anomaly indices were calculated to identify the drought prone areas in the study area. To monitor meteorological drought SPI values were used and NDVI was calculated for agricultural drought. These indices were integrated to compute the spatial and temporal drought maps. Three zones; no drought, slight drought and moderate drought were identified. Final drought map shows that 30.21% of the area faces moderate drought, 28.36% faces slight drought while nearly 41.3% faces no drought situation. Drought prevalence and severity is present more in the southern part of Khushab district than the northern part. Most of the northern part is not under any type of drought. Thus, an overall outcome of this study shows that risk areas can be assessed appropriately by integration of various data sources and thereby management plans can be prepared to deal with the hazard.